Validation of Fuscoporia (Hymenochaetales, Basidiomycota) ITS sequences and five new species based on multi-marker phylogenetic and morphological analyses - Yoonhee Cho; Dohye Kim; Yoongil Lee; Juhwan Jeong; Shahid Hussain; Young Woon Lim (IMA Fungus)
Abstract Although there is a continuous increase in available molecular data, not all sequence identities in public databases are always properly verified and managed. Here, the sequences available in GenBank for Fuscoporia (Hymenochaetales) were validated. Many morphological characters of Fuscoporia overlap among the species, emphasizing the role of molecular identification for accuracy. The identities of 658 Fuscoporia GenBank internal transcribed spacer (ITS) sequences were assessed using ITS phylogeny, revealing 109 (16.6%) misidentified and 196 (29.8%) unspecified sequences. They were validated and re-identified based on the research articles they were published in and, if unpublished, based on sequences from the type, type locality-derived sequences, or otherwise reliable sequences. To enhance the resolution of species delimitation, a phylogenetic assessment of a multi-marker dataset (ITS + nrLSU + rpb2 + tef1) was conducted. The multi-marker phylogeny resolved five of the twelve species complexes found in the ITS phylogeny and uncovered five new Fuscoporia species: F. dolichoseta, F. gilvoides, F. koreana, F. reticulata, and F. semicephala. The validated ITS sequences in this study may prevent further accumulation of misidentified sequences in public databases and contribute to a more accurate taxonomic evaluation of Fuscoporia species.